Stylistic exercise in “Memórias Póstumas de Brás Cubas”, by Machado de Assis - Leite, Ricardo Lopes (2020)
This paper analyzes an excerpt from Machado de Assis’ novel “Memórias Póstumas de Brás Cubas”, with the purpose of examining the stylistic resources used by the writer to translate, into metaphorical terms and with some irony, the moment of the narrator’s death. The analysis is based on aspects of traditional Stylistics, more precisely on the structuralist strand, known as Language stylistics (DUARTE, 2006, DUBOIS, 1974, CÂMARA Jr., 1978, MARTINS, 1989) and intends to identify some aspects that compose what we could call Machado’s style. The paper pays homage to Paulo Mosânio Teixeira Duarte, great admirer of Stylistics and also a researcher into this area, especially into Machado’s work.